Exercise-Induced Changes In Blood Lactate And Muscle Fatigue: A Comparative Study Between Trained And Untrained Individuals - Habib, Zahra; Javed, Najam-ul-Sehar; Ambreen, Shazadi; Hussain, Asma; Imtiaz, Ayesha; Munir, Hina; Aftab, Muhammad Imran; Ali, Madiha (Journal of Neonatal Surgery, 2025)
Background: Exercise induces physiological stress, primarily with elevated blood lactate and muscle fatigue during exercise, particularly anaerobic exercise. Trained respondents respond by enhanced lactate clearance and delayed fatigue development, whereas untrained respondents can be characterized by an acute accumulation of lactate. Learning about these distinctions is useful in the maximization of training programs and corporate performance in athletics and rehabilitation. Objectives: This experiment seeks to determine the feminine differences in plasma lactate versus muscle fatigue rates in untrained subjects and those who are trained during graded exercise to determine the effect of level of training on metabolic stress performance along with recovery kinetics. Study design: A Prospective Study. Place and duration of study: Nishtar Medical University Multan, From May 2024 To May 2025 Methods:A graded treadmill exercise was done by twenty (10 trained and 10 untrained) participants. Baseline, peak and post-exercise blood lactate was assessed by finger-prick acivities. Muscle fatigue was measured through isometric handgrip strength and perceived exertion (RPE). A comparison in the lactate reaction of the participants and fatigue thresholds was performed by providing mean values, standard deviation, and independent t-tests, which indicated statistical significance (p < 0.05). Results: Included applicants were recruited as a sample of 20 participants aged 20-25 years and 10 trained participants (mean 24.6 +/- 2.1 years) and 10 untrained (mean 25.2 +/- 2.4 years). It resulted in the lower peak lactate levels in trained individuals (6.1 +/- 0.8 mol/L) than in untrained individuals (8.4 +/- 1.2 mol/L, p = 0.002). The trained group developed muscle fatigue later (longer handgrip endurance times 52.3 +/- 6.7 sec.) compared to the untrained group (38.5 +/- 5.9 sec., p = 0.001). During recovery, the trained individuals had faster lactate discharge. These distinctions in food patterns imply better metabolism in the trained group. Conclusion: Individuals trained revealed a greater capacity to utilize lactate, increased resistance to fatigue, and experienced faster recovery. These results hold the significance of the physiological advantages of regular training on lactate metabolism fatigue tolerance. These adaptations are paramount in the plan of more effective fitness and rehabilitation programs. Future studies can also examine how different types and intensity of training, and duration effect the management of lactate dynamics and fatigue limits among various populations